Stellera chamaejasme and Its Main Compound Luteolin 7-O-Glucoside Alleviates Skin Lesions in Oxazolone- and 2,4-Dinitrochlorobenzene-Stimulated Murine Models of Atopic Dermatitis - Jo, Beom-Geun; Park, No-June; Jegal, Jonghwan; Choi, Sangho; Lee, Sang Woo; Yi, Li Wan; Kim, Su-Nam; Yang, Min Hye (Planta Medica, 2019)
Stellera chamaejasme, also known as “Langdu”, has been traditionally used for the management of skin-related diseases such as psoriasis and skin ulcers. The aim of this study was to determine whether S. chamaejasme and its major component, luteolin 7-O-glucoside, have a preventive effect on the development of atopic dermatitis in oxazolone-treated BALB/c mice and 2,4-dinitrochlorobenzene-treated hairless mice. The epicutaneous applications of oxazolone and 2,4-dinitrochlorobenzene evoke an experimental murine atopic dermatitis-like reaction in BALB/c mouse ears and SKH-1 hairless mice. Atopic skin symptoms, including erythema (redness), pruritus (itching), exudation (weeping), excoriation (peeling), and lichenification (skin thickening), responded to treatment with S. chamaejasme aerial parts EtOH extract for 2 or 3 weeks. Histopathological examination revealed S. chamaejasme aerial parts EtOH extract significantly reduced inflammatory cell infiltration when applied to atopic dermatitis mice. In addition, luteolin 7-O-glucoside, the major active compound of the S. chamaejasme aerial parts EtOH extract, decreased serum IgE and IL-4 levels and transepidermal water loss and increased skin hydration, therefore exhibiting strong anti-atopic dermatitis activity in 2,4-dinitrochlorobenzene-induced atopic dermatitis mice. In this study, we confirmed antipruritic and antidermatitic effects of S. chamaejasme extract and its main component luteolin 7-O-glucoside in atopic dermatitis murine models. The study shows S. chamaejasme aerial parts EtOH extract and luteolin 7-O-glucoside are most likely to be potential drug candidates for atopic dermatitis treatment.
Keywords: Stellera chamaejasme; Thymelaeaceae; luteolin 7-O-glucoside; atopic dermatitis; skin barrier function; interleukin 4; immunoglobulin E